Healthcare Expenditures : A Comparative Analysis of Nuts 3 Regions in Poland - Weszczak, Anna; Staszek, Aneta (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
This paper is a presentation of healthcare spending in Poland by the construction of spatial econometric model model for NUTS 3 regions in 2008, 2009 and 2010. The study was undertaken due to elucidate the relationship between healthcare spending and economic, demographic and health status variables, such as: income level, the level of fertility, population over 65 years and the number of rural population, unemployment rate and female employment.